Enhancement of blaIMP-carrying plasmid transfer in Klebsiella pneumoniae by hospital wastewater: a transcriptomic study - Jiang, Yuan; Shu, Luting; Wen, Huan; Wei, Yueshuai; Liu, Siyi; Ye, Caihong; Cheng, Ling; Zeng, Zhangrui; Liu, Jinbo (Frontiers in Microbiology, 2025)
IntroductionKlebsiella pneumoniae is a critical ESKAPE pathogen that presents a significant challenge to public health because of its multidrug-resistant strains. This study investigates the impact and mechanisms of hospital wastewater on the horizontal gene transfer of carbapenem resistance genes, particularly blaIMP, in K. pneumoniae.MethodsLB broth was prepared using sterile filtered wastewater as the substrate to investigate the impact of wastewater on the transfer of carbapenem-resistant gene blaIMP in K. pneumoniae. The mechanisms of sewage effects on the horizontal transfer of blaIMP were explored by integrating transcriptome sequencing with the detection of extracellular membrane permeability, intracellular reactive oxygen species (ROS), and other test results.ResultsHospital wastewater significantly enhances the conjugation frequency of plasmids containing blaIMP, showing a two-fold increase in wastewater-based LB broth compared to regular LB broth. In comparison to regular LB broth culture, the wastewater-based LB broth culture group showed significant alterations in the expression of 1,415 genes, with 907 genes upregulated and 508 genes downregulated. Genes related to conjugation transfer systems and the type IV secretion system were significantly upregulated, indicating a potential role in promoting plasmid transfer. Moreover, the treatment of wastewater resulted in elevated intracellular ROS production and increased permeability of bacterial outer membranes, potentially facilitating the spread of antibiotic resistance genes.DiscussionThis research shows that hospital wastewater facilitates the transfer of drug-resistant plasmids containing blaIMP and elucidates its potential mechanisms. A more detailed investigation into these mechanisms may facilitate the prevention of resistance transmission between healthcare and environmental contexts and inform future strategies for managing carbapenem resistance.